Integrating maternal, newborn, child health and non-communicable disease care in the sustainable development goal era - Akselrod, Svetlana; Banerjee, Anshu; Collins, Téa E.; Acharya, Shambhu; Artykova, Nazira; Askew, Ian; Berdzuli, Nino; Diorditsa, Sergey; Eggers, Rudolf; Farrington, Jill; Jakab, Zsuzsanna; Ferreira-Borges, Carina; et al. (Frontiers in Public Health, 2023)
Noncommunicable diseases (NCDs) and maternal newborn and child health (MNCH) are two deeply intertwined health areas that have been artificially separated by global health policies, resource allocations and programming. Optimal MNCH care can provide a unique opportunity to screen for, prevent and manage early signs of NCDs developing in both the woman and the neonate. This paper considers how NCDs, NCD modifiable risk factors, and NCD metabolic risk factors impact MNCH. We argue that integrated management is essential, but this faces challenges that manifest across all levels of domestic health systems. Progress toward Sustainable Development targets requires joined-up action.